A study on the reactivity characteristics of dissolved effluent organic matter (EfOM) from municipal wastewater treatment plant during ozonation. (1st January 2016) - Jin, Pengkang; Jin, Xin; Bjerkelund, Viggo A.; Østerhus, Stein W.; Wang, Xiaochang C.; Yang, Lei
Abstract: The reactivity of dissolved effluent organic matter (EfOM) in the process of ozonation was examined. Under different ozone dosages (0.42 ± 0.09, 0.98 ± 0.11 and 2.24 ± 0.17 mgO3 /mg DOC), the EfOM before and after ozonation could be classified into four fractions according to their hydrophobicities. By ozonation, the hydrophobic fractions, especially hydrophobic acid (HOA) and hydrophobic neutral (HON), were found to undergo a process of transformation into hydrophilic fractions (HI), of which the HOA were first transformed into HON, and then the majority of the HON fraction was later converted to HI by further ozonation. It was noticeable that after ozonation, the fluorescence intensity in the humic-like and protein-like regions decreased as indicated by the excitation and emission matrix (EEM) spectra for the hydrophobic fractions. By coupling the EEM spectra with the molecular size analysis using high performance size exclusion chromatography (HPSEC), the difference between the characteristic distributions of the humic-like and protein-like fluorophores were further revealed. It could thus be extrapolated that ozone might have preferentially reacted with the protein-like hydrophobic fraction with molecular weight (MW) less than 100 kDa. Moreover, by X-ray photoelectron spectroscopy (XPS) analysis, it was identified that with increasing ozone dosage (from 0 to 2.24 ± 0.17 mgO3 /mg DOC), the aromaticity of HON decreased dramatically, while aliphatics and ketones increased especially at the low ozone dose (0.42 ± 0.09 mgO3 /mg DOC). Of the EfOM fractions, the HON fraction would have a higher content of electron enriched aromatics which could preferentially react with ozone rather than the HOA fraction. Graphical abstract: Highlights: EfOMs and their ozonation products were fractionated by their hydrophobicity. Different organic fractions differed each other in their reactivity with ozone. Ozone preferentially reacted with aromatic and protein-like organics of small MW. Ozonation of organics proceeded through a pathway from HOA to HON, and then to HI.